Pemetaan Pola Arus Sungai Mahakam Kabupaten Kutai Kartanegara Menggunakan Software ArcGIS - Fevrin Wardani; Feri Fadlin; Radik Khairil Insanu; Dwi Agung Pramono (Journal of Geomatics Engineering, Technology, and Science, 2024)
This research is undermined by the dynamics of the current patterns of the Mahakam River, which is a crucial element in understanding the waters including the safety of the river transportation. The method used in this study is to take field data horizontally using the Current Meter tool, which is then continued with the analysis process with the help of ArcGIS software. The results of the research show that the speed patterns and direction of the flow of the river have different significance in each depth, as for the direction pattern of the current of the Mahakam River dominates from top to bottom, the cause of the occurrence of different direction of flow due to the topographic factors of the base river.